Mechanisms and Microenvironment Investigation of Cellularized High Density Gradient Collagen Matrices via Densification. (19th February 2016) - Novak, Tyler; Seelbinder, Benjamin; Twitchell, Celina M.; van Donkelaar, Corrinus C.; Voytik‐Harbin, Sherry L.; Neu, Corey P.
Abstract : Biological tissues and biomaterials are often defined by unique spatial gradients in physical properties that impart specialized function over hierarchical scales. The structure of these materials forms continuous transitional gradients and discrete local microenvironments between adjacent (or within) tissues, and across matrix–cell boundaries, which is difficult to replicate with common scaffold systems. Here, the matrix densification of collagen leading to gradients in density, mechanical properties, and fibril morphology is studied. High‐density regions form via a fluid pore pressure and flow‐driven mechanism, with increased relative fibril density (10×), mechanical properties (20×, to 94.40 ± 18.74 kPa), and maximum fibril thickness (1.9×, to >1 μm) compared to low‐density regions, while maintaining porosity and fluid/mass transport to support viability of encapsulated cells. Similar to the organization of the articular cartilage zonal structure, it is found that high‐density collagen regions induce cell and nuclear alignment of primary chondrocytes. Chondrocyte gene expression is maintained in collagen matrices, and no phenotypic changes are observed as a result of densification. Collagen densification provides a tunable platform for the creation of gradient systems to study complex cell–matrix interactions. These methods are easily generalized to compression and boundary condition modalities useful to mimic a broad range of tissues. Abstract : Densification of collagen oligomer matrices via confined compression facilitates the development of a unique, 3D microenvironment and defined physical gradient for use in the study of local cellular interaction and gene expression. Gradient properties in collagen concentration, fibril morphology, and local mechanical properties are induced over a range salient to current microenvironment research and resultant chondrocyte gene expression is investigated.